Nitrogen Levels Effects on Different Maturity Duration Hybrid Rice at Parwanipur, Bara, Nepal - Shah, Pradeep; Sah, Mitali Kumari; Mishra, Anand; Bhattrai, Rajendra Kumar (Agronomy Journal of Nepal, 2023)
Two years field experiments were conducted at Directorate of Agricultural Research, Parwanipur, Bara, Nepal from 2016 to 2017 to assess the effect of different hybrid rice varieties and nitrogen levels on yield attributes, yield and economics of rice. The experiment was arranged in two factorial Randomized Complete Block Design with three replications. The experiment comprised 12 treatment combinations of three different maturity duration hybrid rice varieties (Arize 6129 Gold, Arize Tej Gold and Arize 6444 Gold) and four nitrogen levels (0, 60, 120 and 180 kg ha-1). The two years combine analysis revealed that the hybrid varieties Arize 6444 Gold (4313 kg ha-1) and Arize Tej Gold (4274 kg ha-1) recorded significantly higher grain yield over Arize 6129 Gold (3731 kg ha-1). These two hybrid varieties (Arize 6444 Gold and Arize Tej Gold) also recorded significantly higher plant length and grains panicle-1. The nitrogen level of 180 kg ha-1 recorded significantly the highest grain yield at 6357 kg ha-1. Effective tiller m-2 and grains panicle-1 were significantly higher with nitrogen level of 180 kg ha-1. The thousand grains weight was found significantly higher with 180 kg N ha-1, which was statistically similar with 60 and 120 kg ha-1. Moreover, interaction effect between nitrogen levels and varieties revealed that Arize 6444 Gold and Arize Tej Gold equally produced the highest mean grain yield with 180 kg N ha-1. The highest gross return, net return and B:C ratio were observed with 180 kg N ha-1 with Arize 6444 Gold and ArizeTej Gold. Therefore, 180 kg N ha-1 could be optimum dose for Arize 6444 Gold and Arize Tej Gold for Parwanipur, Bara, Nepal.